Prognostic factors for survival in patients on hemodialysis - Tapia Zerpa, Carlos Enrique (2024)
Objective: To determine the overall survival of patients on hemodialysis and prognostic factors associated. Methods: A retrospective cohort of patients who entered a chronic hemodialysis program at the Centro Nacional de Salud Renal of EsSALUD from 1994 and 2014. A total of 1789 patients were included, and data was gathered from the SIG version 2.0, which stores charts since 1994. The survival of the cohort and prognostic factors were evaluated. Results: Mean age was 49.7 ± 17.4 years; 779 (43.5%) were females; 393 (22%) were diabetics, and 592 (33.2%) had blood hypertension; 1408 (83%) had an arterio-venous fistula; 147 (8.16%) had positive serology for hepatitis C; 999 (55.84%) were admitted from 1994 to 2003 and 790 (44,16%) from 2003 to 2014. Survival of the cohort did not change by sex, presence of hypertension, serology at admission, or decade of admission.  Multivariate analysis identified the age group above 50 years [HR: 3.72 (IC95%: 3.07 – 4.50) p = 0.000] and use of catheters at admission to the chronic dialysis program [HR: 1.37 (IC95%: 1.07 – 1.76): p = 0.010] as independent factors for lower survival. Conclusions: The survival was not affected by the decade of admission but by advanced age and use of catheters in the 20-year follow-up period.